2021
DOI: 10.1136/rapm-2020-102225
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a bioabsorbable device that seals perforations after Tuohy needle dural puncture in an ovine model

Abstract: BackgroundWe designed a device to close accidental dural puncture via the offending puncturing epidural needle directly after diagnosis of the puncture and before removing the needle. The aim of this study was to quantify this device’s ability to seal cerebrospinal fluid leakage.MethodsForty-six anesthetized adult sheep were studied in a single-blind randomized controlled fashion in two equal groups.An intentional dural puncture was performed with an 18-gage Tuohy needle on all the sheep between L6 and S1 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Currently in the animal experimentation phase, resorbable devices that attempt to seal the hole produced by the Tuohy needle represent a novel and welcome direction in treating the complications of UDP. 68 Additionally, future research is needed to determine which candidates may be at higher risk for an epidural. A small, prospective study suggested that patients with connective tissue disorders are more likely to develop spontaneous intracranial hypotension, and perhaps this subset of women should be screened for prior to epidural placement.…”
Section: Future Direc Tionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently in the animal experimentation phase, resorbable devices that attempt to seal the hole produced by the Tuohy needle represent a novel and welcome direction in treating the complications of UDP. 68 Additionally, future research is needed to determine which candidates may be at higher risk for an epidural. A small, prospective study suggested that patients with connective tissue disorders are more likely to develop spontaneous intracranial hypotension, and perhaps this subset of women should be screened for prior to epidural placement.…”
Section: Future Direc Tionsmentioning
confidence: 99%
“…Future areas of basic and clinical research together with anesthesiologists should aim to determine why the dura fails to heal for some people and how to repair it. Currently in the animal experimentation phase, resorbable devices that attempt to seal the hole produced by the Tuohy needle represent a novel and welcome direction in treating the complications of UDP 68 . Additionally, future research is needed to determine which candidates may be at higher risk for an epidural.…”
Section: Future Directionsmentioning
confidence: 99%